1986
DOI: 10.1128/jvi.59.3.660-668.1986
|View full text |Cite
|
Sign up to set email alerts
|

Putative glycoprotein gene of varicella-zoster virus with variable copy numbers of a 42-base-pair repeat sequence has homology to herpes simplex virus glycoprotein C

Abstract: A strain variation of varicella-zoster virus that maps to the UL region of the genome was found to be due to different copy numbers of a high GC 42-base-pair repeat. DNA sequence analysis of this variable region showed the sequence to be 5-GCGGGATCGGGCTTTCGGG(A/T)AGCGGCCGAGGTGGGCGCGACG-3. Strains Scott and Webster both contain 7 and 32 copies of the repeat, whereas strain Oka has exactly 4 copies less. Microheterogeneity exists within the repeated sequences, depending on the strain and the repeat number. MATER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…There are a number of gC homologs found in other herpesviruses (1,6,35,55); these gC homologs contain areas homologous to the C3b-binding regions I, II, and III. Although only one of these viruses, equine herpesvirus, has been demonstrated to bind human C3b on the surface of infected cells (5), it is possible that the others are similar to gC-2 and will bind C3b when the protein is purified and tested in direct binding assays.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of gC homologs found in other herpesviruses (1,6,35,55); these gC homologs contain areas homologous to the C3b-binding regions I, II, and III. Although only one of these viruses, equine herpesvirus, has been demonstrated to bind human C3b on the surface of infected cells (5), it is possible that the others are similar to gC-2 and will bind C3b when the protein is purified and tested in direct binding assays.…”
Section: Discussionmentioning
confidence: 99%
“…Since this study has further demonstrated that R5 is variable among VZV strains, all direct reiterations of VZV except R3 are now known to vary among VZV Strains. Tandem direct repeats in general seem to be variable among VZV strains, whether or not they are part of coding regions, since Rl and R2 are present within open reading frames (3,8), whereas R4 and R5 are not (1,3). Although the mechanism by which they change is not known at present, tandem direct reiterations of the VZV genome are hot spots that vary much more readily than other regions of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…All probes were double-stranded DNA fragments labeled to high specific activity by using oligonucleotide-primed repair synthesis and [␣-32 P]dCTP (3,000 Ci/mmol). Each specific probe was generated from previously derived DNA clones from VZV strain Scott, a low-passage clinical isolate (25). VZV gC-specific probes were generated by using a BstN1-AhdI fragment, representing bp 19480 to 21116.…”
Section: Methodsmentioning
confidence: 99%
“…Diminished expression of glycoprotein C (gC) has been proposed as a genetic factor that may be related to the clinical attenuation of V-Oka (24). gC is one of six known VZV envelope glycoproteins and has 34% amino acid homology to herpes simplex virus type 1 (HSV-1) gC (25). HSV-1 gC binds to heparan sulfate on the cell surface and to the C3b component of complement (16,21).…”
mentioning
confidence: 99%